## Engage NY Eureka Math 5th Grade Module 3 Lesson 9 Answer Key

### Eureka Math Grade 5 Module 3 Lesson 9 Sprint Answer Key

A

Add and Subtract Fractions with Like Units

Question 1.

\(\frac{1}{5}\) + \(\frac{1}{5}\) =

Answer:

\(\frac{1}{5}\) + \(\frac{1}{5}\) = \(\frac{2}{5}\)

Question 2.

\(\frac{1}{10}\) + \(\frac{5}{10}\) =

Answer:

\(\frac{1}{10}\) + \(\frac{5}{10}\) = \(\frac{6}{10}\) = \(\frac{3}{5}\)

Question 3.

\(\frac{1}{10}\) + \(\frac{7}{10}\) =

Answer:

\(\frac{1}{10}\) + \(\frac{7}{10}\) = \(\frac{8}{10}\) = \(\frac{4}{5}\)

Question 4.

\(\frac{2}{5}\) + \(\frac{2}{5}\) =

Answer:

\(\frac{2}{5}\) + \(\frac{2}{5}\) = \(\frac{4}{5}\)

Question 5.

\(\frac{5}{10}\) – \(\frac{4}{10}\) =

Answer:

\(\frac{5}{10}\) – \(\frac{4}{10}\) = \(\frac{1}{10}\)

Question 6.

\(\frac{3}{5}\) – \(\frac{1}{5}\) =

Answer:

\(\frac{3}{5}\) – \(\frac{1}{5}\) = \(\frac{2}{5}\)

Question 7.

\(\frac{3}{10}\) + \(\frac{3}{10}\) =

Answer:

\(\frac{3}{10}\) + \(\frac{3}{10}\) = \(\frac{6}{10}\) = \(\frac{3}{5}\)

Question 8.

\(\frac{4}{5}\) – \(\frac{1}{5}\) =

Answer:

\(\frac{4}{5}\) – \(\frac{1}{5}\) = \(\frac{3}{5}\)

Question 9.

\(\frac{1}{4}\) + \(\frac{1}{4}\) =

Answer:

\(\frac{1}{4}\) + \(\frac{1}{4}\) = \(\frac{2}{4}\) = \(\frac{1}{2}\)

Question 10.

\(\frac{1}{4}\) + \(\frac{2}{4}\) =

Answer:

\(\frac{1}{4}\) + \(\frac{2}{4}\) = \(\frac{3}{4}\)

Question 11.

\(\frac{3}{12}\) – \(\frac{2}{12}\) =

Answer:

\(\frac{3}{12}\) – \(\frac{2}{12}\) = \(\frac{1}{12}\)

Question 12.

\(\frac{1}{4}\) + \(\frac{3}{4}\) =

Answer:

\(\frac{1}{4}\) + \(\frac{3}{4}\) = \(\frac{4}{4}\) = 1

Question 13.

\(\frac{1}{12}\) + \(\frac{1}{12}\) =

Answer:

\(\frac{1}{12}\) + \(\frac{1}{12}\) = \(\frac{2}{12}\) = \(\frac{1}{6}\)

Question 14.

\(\frac{1}{3}\) + \(\frac{1}{3}\) =

Answer:

\(\frac{1}{3}\) + \(\frac{1}{3}\) = \(\frac{2}{3}\)

Question 15.

\(\frac{3}{12}\) – \(\frac{2}{12}\) =

Answer:

\(\frac{3}{12}\) – \(\frac{2}{12}\) = \(\frac{1}{12}\)

Question 16.

\(\frac{5}{12}\) + \(\frac{6}{12}\) =

Answer:

\(\frac{5}{12}\) + \(\frac{6}{12}\) = \(\frac{11}{12}\)

Question 17.

\(\frac{7}{12}\) + \(\frac{4}{12}\) =

Answer:

\(\frac{7}{12}\) + \(\frac{4}{12}\) = \(\frac{11}{12}\)

Question 18.

\(\frac{4}{6}\) – \(\frac{1}{6}\) =

Answer:

\(\frac{4}{6}\) – \(\frac{1}{6}\) = \(\frac{3}{6}\) = \(\frac{1}{2}\)

Question 19.

\(\frac{1}{6}\) + \(\frac{2}{6}\) =

Answer:

\(\frac{1}{6}\) + \(\frac{2}{6}\) = \(\frac{3}{6}\) = \(\frac{1}{2}\)

Question 20.

\(\frac{1}{6}\) + \(\frac{1}{6}\) + \(\frac{1}{6}\) =

Answer:

\(\frac{1}{6}\) + \(\frac{1}{6}\) + \(\frac{1}{6}\) = \(\frac{3}{6}\) =Â \(\frac{1}{2}\)

Question 21.

\(\frac{1}{3}\) + \(\frac{1}{3}\) + \(\frac{1}{3}\) =

Answer:

\(\frac{1}{3}\) + \(\frac{1}{3}\) + \(\frac{1}{3}\) = \(\frac{3}{3}\) = 1

Question 22.

\(\frac{1}{12}\) + \(\frac{1}{12}\) + \(\frac{1}{12}\) =

Answer:

\(\frac{1}{12}\) + \(\frac{1}{12}\) + \(\frac{1}{12}\) = \(\frac{3}{12}\) = \(\frac{1}{4}\)

Question 23.

\(\frac{1}{9}\) + \(\frac{1}{9}\) + \(\frac{1}{9}\) =

Answer:

\(\frac{1}{9}\) + \(\frac{1}{9}\) + \(\frac{1}{9}\) = \(\frac{3}{9}\) =Â \(\frac{1}{3}\)

Question 24.

\(\frac{1}{9}\) + \(\frac{3}{9}\) + \(\frac{1}{9}\) =

Answer:

\(\frac{1}{9}\) + \(\frac{3}{9}\) + \(\frac{1}{9}\) = \(\frac{5}{9}\)

Question 25.

\(\frac{4}{9}\) – \(\frac{1}{9}\) – \(\frac{3}{9}\) =

Answer:

\(\frac{4}{9}\) – \(\frac{1}{9}\) – \(\frac{3}{9}\) = \(\frac{8}{9}\)

Question 26.

\(\frac{1}{4}\) + \(\frac{2}{4}\) + \(\frac{1}{4}\) =

Answer:

\(\frac{1}{4}\) + \(\frac{2}{4}\) + \(\frac{1}{4}\) = \(\frac{4}{4}\) = 1

Question 27.

\(\frac{1}{8}\) + \(\frac{3}{8}\) + \(\frac{2}{8}\) =

Answer:

\(\frac{1}{8}\) + \(\frac{3}{8}\) + \(\frac{2}{8}\) = \(\frac{6}{8}\) = \(\frac{3}{4}\)

Question 28.

\(\frac{5}{12}\) + \(\frac{1}{12}\) + \(\frac{5}{12}\) =

Answer:

\(\frac{5}{12}\) + \(\frac{1}{12}\) + \(\frac{5}{12}\) = \(\frac{11}{12}\)

Question 29.

\(\frac{2}{9}\) + \(\frac{3}{9}\) + \(\frac{2}{9}\) =

Answer:

\(\frac{2}{9}\) + \(\frac{3}{9}\) + \(\frac{2}{9}\) = \(\frac{7}{9}\)

Question 30.

\(\frac{3}{10}\) – \(\frac{3}{10}\) + \(\frac{3}{10}\) =

Answer:

\(\frac{3}{10}\) – \(\frac{3}{10}\) + \(\frac{3}{10}\) = \(\frac{9}{10}\)

Question 31.

\(\frac{3}{5}\) – \(\frac{1}{5}\) – \(\frac{1}{5}\) =

Answer:

\(\frac{3}{5}\) – \(\frac{1}{5}\) – \(\frac{1}{5}\) = \(\frac{3}{5}\) – \(\frac{2}{5}\) = \(\frac{1}{5}\)

Question 32.

\(\frac{1}{6}\) + \(\frac{2}{6}\) =

Answer:

\(\frac{1}{6}\) + \(\frac{2}{6}\) = \(\frac{3}{6}\) = \(\frac{1}{2}\) =\

Question 33.

\(\frac{3}{12}\) + \(\frac{4}{12}\) =

Answer:

\(\frac{3}{12}\) + \(\frac{4}{12}\) = \(\frac{7}{12}\)

Question 34.

\(\frac{3}{12}\) + \(\frac{6}{12}\) =

Answer:

\(\frac{3}{12}\) + \(\frac{6}{12}\) = \(\frac{9}{12}\) = \(\frac{3}{4}\)

Question 35.

\(\frac{4}{8}\) + \(\frac{2}{8}\) =

Answer:

\(\frac{4}{8}\) + \(\frac{2}{8}\) = \(\frac{6}{8}\) = \(\frac{3}{4}\)

Question 36.

\(\frac{4}{12}\) + \(\frac{1}{12}\) =

Answer:

\(\frac{4}{12}\) + \(\frac{1}{12}\) = \(\frac{5}{12}\)

Question 37.

\(\frac{1}{5}\) + \(\frac{3}{5}\) =

Answer:

\(\frac{1}{5}\) + \(\frac{3}{5}\) = \(\frac{4}{5}\)

Question 38.

\(\frac{2}{5}\) + \(\frac{2}{5}\) =

Answer:

\(\frac{2}{5}\) + \(\frac{2}{5}\) = \(\frac{4}{5}\)

Question 39.

\(\frac{1}{6}\) + \(\frac{2}{6}\) =

Answer:

\(\frac{1}{6}\) + \(\frac{2}{6}\) = \(\frac{3}{6}\) = \(\frac{1}{2}\)

Question 40.

\(\frac{5}{12}\) – \(\frac{3}{12}\) =

Answer:

\(\frac{5}{12}\) – \(\frac{3}{12}\) = \(\frac{2}{12}\) = \(\frac{1}{6}\)

Question 41.

\(\frac{7}{15}\) – \(\frac{2}{15}\) =

Answer:

\(\frac{7}{15}\) – \(\frac{2}{15}\) = \(\frac{5}{15}\) = \(\frac{1}{3}\)

Question 42.

\(\frac{7}{15}\) – \(\frac{3}{15}\) =

Answer:

\(\frac{7}{15}\) – \(\frac{3}{15}\) = \(\frac{4}{15}\)

Question 43.

\(\frac{11}{15}\) – \(\frac{2}{15}\) =

Answer:

\(\frac{11}{15}\) – \(\frac{2}{15}\) = \(\frac{9}{15}\)

Question 44.

\(\frac{2}{15}\) + \(\frac{4}{15}\) =

Answer:

\(\frac{2}{15}\) + \(\frac{4}{15}\) = \(\frac{6}{15}\) = \(\frac{2}{5}\)

B

Add and Subtract Fractions with Like Units

Question 1.

\(\frac{1}{2}\) + \(\frac{1}{2}\) =

Answer:

\(\frac{1}{2}\) + \(\frac{1}{2}\) = \(\frac{2}{2}\) = 1

Question 2.

\(\frac{2}{8}\) + \(\frac{1}{8}\) =

Answer:

\(\frac{2}{8}\) + \(\frac{1}{8}\) = \(\frac{3}{8}\)

Question 3.

\(\frac{2}{8}\) + \(\frac{3}{8}\) =

Answer:

\(\frac{2}{8}\) + \(\frac{3}{8}\) = \(\frac{5}{8}\)

Question 4.

\(\frac{2}{12}\) – \(\frac{1}{12}\) =

Answer:

\(\frac{2}{12}\) – \(\frac{1}{12}\) = \(\frac{1}{12}\)

Question 5.

\(\frac{5}{12}\) + \(\frac{2}{12}\) =

Answer:

\(\frac{5}{12}\) + \(\frac{2}{12}\) = \(\frac{7}{12}\)

Question 6.

\(\frac{4}{8}\) – \(\frac{3}{8}\) =

Answer:

\(\frac{4}{8}\) – \(\frac{3}{8}\) = \(\frac{1}{8}\)

Question 7.

\(\frac{4}{8}\) – \(\frac{3}{8}\) =

Answer:

\(\frac{4}{8}\) – \(\frac{3}{8}\) = \(\frac{1}{8}\)

Question 8.

\(\frac{1}{8}\) + \(\frac{5}{8}\) =

Answer:

\(\frac{1}{8}\) + \(\frac{5}{8}\) = \(\frac{6}{8}\) = \(\frac{3}{4}\)

Question 9.

\(\frac{3}{4}\) – \(\frac{1}{4}\) =

Answer:

\(\frac{3}{4}\) – \(\frac{1}{4}\) = \(\frac{2}{4}\) = \(\frac{1}{2}\)

Question 10.

\(\frac{3}{6}\) – \(\frac{3}{6}\) =

Answer:

\(\frac{3}{6}\) – \(\frac{3}{6}\) = 0

Question 11.

\(\frac{3}{9}\) + \(\frac{3}{9}\) =

Answer:

\(\frac{3}{9}\) + \(\frac{3}{9}\) = \(\frac{6}{9}\) = \(\frac{2}{3}\)

Question 12.

\(\frac{2}{3}\) + \(\frac{1}{3}\) =

Answer:

\(\frac{2}{3}\) + \(\frac{1}{3}\) = \(\frac{3}{3}\) = 1

Question 13.

\(\frac{6}{9}\) – \(\frac{4}{9}\) =

Answer:

\(\frac{6}{9}\) – \(\frac{4}{9}\) = \(\frac{2}{9}\)

Question 14.

\(\frac{5}{9}\) – \(\frac{3}{9}\) =

Answer:

\(\frac{5}{9}\) – \(\frac{3}{9}\) = \(\frac{2}{9}\)

Question 15.

\(\frac{2}{9}\) + \(\frac{2}{9}\) =

Answer:

\(\frac{2}{9}\) + \(\frac{2}{9}\) = \(\frac{4}{9}\)

Question 16.

\(\frac{1}{12}\) + \(\frac{3}{12}\) =

Answer:

\(\frac{1}{12}\) + \(\frac{3}{12}\) = \(\frac{4}{12}\) = \(\frac{1}{4}\)

Question 17.

\(\frac{5}{12}\) – \(\frac{4}{12}\) =

Answer:

\(\frac{5}{12}\) – \(\frac{4}{12}\) = \(\frac{1}{12}\)

Question 18.

\(\frac{9}{12}\) – \(\frac{6}{12}\) =

Answer:

\(\frac{9}{12}\) – \(\frac{6}{12}\) = \(\frac{3}{12}\) = \(\frac{1}{4}\)

Question 19.

\(\frac{6}{10}\) – \(\frac{4}{10}\) =

Answer:

\(\frac{6}{10}\) – \(\frac{4}{10}\) = \(\frac{2}{10}\) = \(\frac{1}{5}\)

Question 20.

\(\frac{2}{8}\) + \(\frac{2}{8}\) + \(\frac{2}{8}\) =

Answer:

\(\frac{2}{8}\) + \(\frac{2}{8}\) + \(\frac{2}{8}\) = \(\frac{6}{8}\) = \(\frac{3}{4}\)

Question 21.

\(\frac{1}{10}\) + \(\frac{1}{10}\) + \(\frac{1}{10}\) =

Answer:

\(\frac{1}{10}\) + \(\frac{1}{10}\) + \(\frac{1}{10}\) = \(\frac{3}{10}\) +

Question 22.

\(\frac{7}{12}\) – \(\frac{2}{10}\) – \(\frac{4}{10}\) =

Answer:

\(\frac{7}{12}\) – \(\frac{2}{10}\) – \(\frac{4}{10}\) = \(\frac{7}{12}\) – \(\frac{6}{10}\) = \(\frac{1}{10}\)

Question 23.

\(\frac{1}{12}\) + \(\frac{6}{12}\) + \(\frac{2}{12}\) =

Answer:

\(\frac{1}{12}\) + \(\frac{6}{12}\) + \(\frac{2}{12}\) = \(\frac{9}{12}\) = \(\frac{3}{4}\)

Question 24.

\(\frac{4}{12}\) + \(\frac{3}{12}\) + \(\frac{3}{12}\) =

Answer:

\(\frac{4}{12}\) + \(\frac{3}{12}\) + \(\frac{3}{12}\) = \(\frac{10}{12}\) = \(\frac{5}{6}\)

Question 25.

\(\frac{8}{12}\) – \(\frac{4}{12}\) – \(\frac{4}{12}\) =

Answer:

\(\frac{8}{12}\) – \(\frac{4}{12}\) – \(\frac{4}{12}\) = \(\frac{8}{12}\) – \(\frac{8}{12}\) = 0

Question 26.

\(\frac{1}{10}\) + \(\frac{2}{10}\) + \(\frac{4}{10}\) =

Answer:

\(\frac{1}{10}\) + \(\frac{2}{10}\) + \(\frac{4}{10}\) = \(\frac{7}{10}\)

Question 27.

\(\frac{1}{10}\) + \(\frac{1}{10}\) + \(\frac{6}{10}\) =

Answer:

\(\frac{1}{10}\) + \(\frac{1}{10}\) + \(\frac{6}{10}\) = \(\frac{8}{10}\) = \(\frac{4}{5}\)

Question 28.

\(\frac{4}{6}\) + \(\frac{1}{6}\) + \(\frac{1}{6}\) =

Answer:

\(\frac{4}{6}\) + \(\frac{1}{6}\) + \(\frac{1}{6}\) = \(\frac{6}{6}\) = 1

Question 29.

\(\frac{2}{12}\) + \(\frac{3}{12}\) + \(\frac{4}{12}\) =

Answer:

\(\frac{2}{12}\) + \(\frac{3}{12}\) + \(\frac{4}{12}\) = \(\frac{9}{12}\) = \(\frac{3}{4}\)

Question 30.

\(\frac{2}{10}\) + \(\frac{4}{10}\) + \(\frac{4}{10}\) =

Answer:

\(\frac{2}{10}\) + \(\frac{4}{10}\) + \(\frac{4}{10}\) = \(\frac{10}{10}\) = 1

Question 31.

\(\frac{3}{10}\) + \(\frac{1}{10}\) + \(\frac{2}{10}\) =

Answer:

\(\frac{3}{10}\) + \(\frac{1}{10}\) + \(\frac{2}{10}\) = \(\frac{6}{10}\) = \(\frac{3}{5}\)

Question 32.

\(\frac{4}{6}\) – \(\frac{2}{6}\) =

Answer:

\(\frac{4}{6}\) – \(\frac{2}{6}\) = \(\frac{2}{6}\) = \(\frac{1}{3}\)

Question 33.

\(\frac{3}{12}\) – \(\frac{2}{12}\) =

Answer:

\(\frac{3}{12}\) – \(\frac{2}{12}\) = \(\frac{1}{12}\)

Question 34.

\(\frac{2}{3}\) + \(\frac{1}{3}\) =

Answer:

\(\frac{2}{3}\) + \(\frac{1}{3}\) = \(\frac{3}{3}\) = 1

Question 35.

\(\frac{2}{4}\) + \(\frac{1}{4}\) =

Answer:

\(\frac{2}{4}\) + \(\frac{1}{4}\) = \(\frac{3}{4}\)

Question 36.

\(\frac{3}{12}\) + \(\frac{2}{12}\) =

Answer:

\(\frac{3}{12}\) + \(\frac{2}{12}\) = \(\frac{5}{12}\)

Question 37.

\(\frac{1}{5}\) + \(\frac{2}{5}\) =

Answer:

\(\frac{1}{5}\) + \(\frac{2}{5}\) = \(\frac{3}{5}\)

Question 38.

\(\frac{4}{5}\) – \(\frac{4}{5}\) =

Answer:

\(\frac{4}{5}\) – \(\frac{4}{5}\) = 0

Question 39.

\(\frac{5}{12}\) – \(\frac{1}{12}\) =

Answer:

\(\frac{5}{12}\) – \(\frac{1}{12}\) = \(\frac{4}{12}\) = \(\frac{1}{3}\)

Question 40.

\(\frac{6}{8}\) + \(\frac{2}{8}\) =

Answer:

\(\frac{6}{8}\) + \(\frac{2}{8}\) = \(\frac{8}{8}\) = 1

Question 41.

\(\frac{2}{8}\) + \(\frac{2}{8}\) + \(\frac{2}{8}\) =

Answer:

\(\frac{2}{8}\) + \(\frac{2}{8}\) + \(\frac{2}{8}\) = \(\frac{6}{8}\) = \(\frac{3}{4}\)

Question 42.

\(\frac{9}{10}\) – \(\frac{7}{10}\) – \(\frac{1}{10}\) =

Answer:

\(\frac{9}{10}\) – \(\frac{7}{10}\) – \(\frac{1}{10}\) = \(\frac{9}{10}\) – \(\frac{8}{10}\) = \(\frac{1}{10}\) =

Question 43.

\(\frac{2}{10}\) + \(\frac{5}{10}\) + \(\frac{2}{10}\) =

Answer:

\(\frac{2}{10}\) + \(\frac{5}{10}\) + \(\frac{2}{10}\) = \(\frac{9}{10}\)

Question 44.

\(\frac{9}{12}\) – \(\frac{1}{12}\) – \(\frac{4}{12}\) =

Answer:

\(\frac{9}{12}\) – \(\frac{1}{12}\) – \(\frac{4}{12}\) = \(\frac{9}{12}\) – \(\frac{5}{12}\) = \(\frac{4}{12}\) = \(\frac{1}{3}\)Â .

### Eureka Math Grade 5 Module 3 Lesson 9 Problem Set Answer Key

Question 1.

First make like units, and then add.

a. \(\frac{3}{4}\) + \(\frac{1}{7}\) =

b. \(\frac{1}{4}\) + \(\frac{9}{8}\) =

c. \(\frac{3}{8}\) + \(\frac{3}{7}\) =

d. \(\frac{4}{9}\) + \(\frac{4}{7}\) =

e. \(\frac{1}{5}\) + \(\frac{2}{3}\) =

f. \(\frac{3}{4}\) + \(\frac{5}{6}\) =

g. \(\frac{2}{3}\) + \(\frac{1}{11}\) =

h. \(\frac{3}{4}\) + 1\(\frac{1}{10}\) =

Answer:

a.

\(\frac{3}{4}\) + \(\frac{1}{7}\)

lcm of 4 and 7 is 28

=\(\frac{21}{28}\) + \(\frac{4}{28}\) = \(\frac{25}{28}\)

b.

\(\frac{1}{4}\) + \(\frac{9}{8}\)

lcm of 4 and 8 is 8

\(\frac{2}{8}\) + \(\frac{9}{8}\) =\(\frac{11}{8}\) = 1\(\frac{3}{8}\)

c.

\(\frac{3}{8}\) + \(\frac{3}{7}\)

lcm of 8 and 7 is 56

\(\frac{21}{56}\) + \(\frac{24}{56}\) = \(\frac{45}{56}\)

d.

\(\frac{4}{9}\) + \(\frac{4}{7}\)

lcm of 9 and 7 is 63

\(\frac{28}{63}\) + \(\frac{36}{63}\) = \(\frac{64}{63}\) = 1\(\frac{1}{63}\)

e.

\(\frac{1}{5}\) + \(\frac{2}{3}\)

lcm of 5 and 3 is 15 .

\(\frac{3}{15}\) + \(\frac{10}{15}\) = \(\frac{13}{15}\)

f.

\(\frac{3}{4}\) + \(\frac{5}{6}\)

lcm of 4 and 6 is 12.

\(\frac{9}{12}\) + \(\frac{10}{12}\) = \(\frac{19}{12}\) =1 \(\frac{7}{12}\)

g.

\(\frac{2}{3}\) + \(\frac{1}{11}\)

lcm of 3 and 11 is 33

\(\frac{22}{33}\) + \(\frac{3}{33}\) = \(\frac{25}{33}\)

h.

\(\frac{3}{4}\) + 1\(\frac{1}{10}\) = \(\frac{3}{4}\) + \(\frac{11}{10}\)

lcm of 4 and 10 is 20.

\(\frac{15}{20}\) + \(\frac{22}{10}\) = \(\frac{37}{20}\) = 1\(\frac{17}{20}\)

Question 2.

Whitney says that to add fractions with different denominators, you always have to multiply the denominators to find the common unit; for example:

\(\frac{1}{4}+\frac{1}{6}=\frac{6}{24}+\frac{4}{24}\)

Show Whitney how she could have chosen a denominator smaller than 24, and solve the problem.

Answer:

multiples of 4 and 6 are

4 : 4, 8, 12, 16, 20, 24

6: 6, 12, 18, 24, 30 .

12 and 24 are the common multiplies of 4 and 6. smaller than 24 we get 12 multiple .

(\(\frac{1 Ã— 3}{4 Ã— 3}\)) + (\(\frac{1 Ã— 2}{6 Ã— 2}\)) = \(\frac{3}{12}\) + \(\frac{2}{12}\) = \(\frac{5}{12}\)

Question 3.

Jackie brought \(\frac{3}{4}\) of a gallon of iced tea to the party. Bill brought \(\frac{7}{8}\) of a gallon of iced tea to the same party. How much iced tea did Jackie and Bill bring to the party?

Answer:

Fraction of iced tea brought by Jackie = \(\frac{3}{4}\)

Fraction of iced tea brought by Bill = \(\frac{7}{8}\)

Total Fraction of iced tea brought to party = \(\frac{3}{4}\) + \(\frac{7}{8}\)Â = \(\frac{6}{8}\) + \(\frac{7}{8}\) = \(\frac{13}{8}\) = 1\(\frac{5}{8}\)

Therefore, Total Fraction of iced tea brought to party = \(\frac{13}{8}\) = 1\(\frac{5}{8}\) .

Question 4.

Madame Curie made some radium in her lab. She used \(\frac{2}{5}\) kg of the radium in an experiment and had 1\(\frac{1}{4}\) kg left. How much radium did she have at first? (Extension: If she performed the experiment twice, how much radium would she have left?)

Answer:

Quantity of Radium made by Madam Curie = x kgs

Fraction of Quantity of Radium used by Experiment = \(\frac{2}{5}\) kg

Fraction of Quantity of Radium left = 1\(\frac{1}{4}\) kg = \(\frac{5}{4}\) kg

Quantity of Radium made by Madam Curie = \(\frac{2}{5}\) + \(\frac{5}{4}[/latex

lcm of 5 and 4 is 20 .

[latex]\frac{8}{20}\)Â + \(\frac{25}{20}\) = \(\frac{33}{20}\) =1\(\frac{13}{20}\) .

Therefore if the experiment is done once the Total Quantity = \(\frac{33}{20}\) =1\(\frac{13}{20}\)

If the Experiment if done twiced .

Total Quantity – Quantity Used for Experiment twice = left Quantity .

\(\frac{33}{20}\) – 2 Ã— \(\frac{2}{5}\) = \(\frac{33}{20}\) –Â \(\frac{4}{5}\) = \(\frac{33}{20}\) – \(\frac{16}{20}\) = \(\frac{17}{20}\)

Therefore if the experiment is done once the Total Quantity = \(\frac{17}{20}\)

### Eureka Math Grade 5 Module 3 Lesson 9 Exit Ticket Answer Key

Make like units, and then add.

a. \(\frac{1}{6}\) + \(\frac{3}{4}\) =

b. 1\(\frac{1}{2}\) + \(\frac{2}{5}\) =

Answer:

a.

\(\frac{1}{6}\) + \(\frac{3}{4}\)

lcm of 6 and 4 is 12

\(\frac{2}{12}\) + \(\frac{9}{12}\) = \(\frac{11}{12}\)

b.

1\(\frac{1}{2}\) + \(\frac{2}{5}\) = \(\frac{3}{2}\) + \(\frac{2}{5}\)

lcm of 2 and 5 is 10.

\(\frac{15}{10}\) + \(\frac{4}{10}\) =\(\frac{19}{10}\) = 1\(\frac{9}{10}\)

### Eureka Math Grade 5 Module 3 Lesson 9 Homework Answer Key

Question 1.

Make like units, and then add.

a. \(\frac{3}{5}\) + \(\frac{1}{3}\) =

b. \(\frac{3}{5}\) + \(\frac{1}{11}\) =

c. \(\frac{2}{9}\) + \(\frac{5}{6}\) =

d. \(\frac{2}{5}\) + \(\frac{1}{4}\) + \(\frac{1}{10}\) =

e. \(\frac{1}{3}\) + \(\frac{7}{5}\) =

f. \(\frac{5}{8}\) + \(\frac{7}{12}\) =

g. 1\(\frac{1}{3}\) + \(\frac{3}{4}\) =

h. \(\frac{5}{6}\) + 1\(\frac{1}{4}\) =

Answer:

a.

\(\frac{3}{5}\) + \(\frac{1}{3}\)

lcm of 5 and 3 is 15

\(\frac{9}{15}\) + \(\frac{5}{15}\) = \(\frac{14}{15}\)

b.

\(\frac{3}{5}\) + \(\frac{1}{11}\)

lcm of 5 and 11 is 55

\(\frac{33}{55}\) + \(\frac{5}{55}\) = \(\frac{38}{55}\)

c.

\(\frac{2}{9}\) + \(\frac{5}{6}\)

lcm of 9 and 6 is 18 .

\(\frac{4}{18}\) + \(\frac{15}{18}\) = \(\frac{19}{18}\) = 1 \(\frac{1}{18}\)

d.

\(\frac{2}{5}\) + \(\frac{1}{4}\) + \(\frac{1}{10}\)

lcm of 5 , 4 and 10 is 20 .

\(\frac{8}{20}\) + \(\frac{5}{20}\) + \(\frac{2}{20}\) = \(\frac{15}{20}\)= \(\frac{3}{4}\)

e.

\(\frac{1}{3}\) + \(\frac{7}{5}\)

lcm of 3 and 5 is 15 .

\(\frac{5}{15}\) + \(\frac{21}{15}\) =\(\frac{26}{3}\) =1\(\frac{11}{15}\)

f.

\(\frac{5}{8}\) + \(\frac{7}{12}\)

lcm of 8 and 12 is 24.

\(\frac{15}{24}\) + \(\frac{14}{24}\) = \(\frac{29}{24}\) = 1\(\frac{5}{24}\)

g.

1\(\frac{1}{3}\) + \(\frac{3}{4}\) = \(\frac{4}{3}\) + \(\frac{3}{4}\)

lcm of 3 and 4Â is 12

\(\frac{16}{12}\) + \(\frac{9}{12}\) = \(\frac{25}{12}\) = 2 \(\frac{1}{12}\)

h.

\(\frac{5}{6}\) + 1\(\frac{1}{4}\) =\(\frac{5}{6}\) + \(\frac{5}{4}\)

lcm of 4 and 6 is 12 .

\(\frac{10}{12}\) + \(\frac{15}{12}\) = \(\frac{25}{12}\) = 2\(\frac{1}{12}\)

Question 2.

On Monday, Ka practiced guitar for \(\frac{2}{3}\) of one hour. When she finished, she practiced piano for \(\frac{3}{4}\) of one hour. How much time did Ka spend practicing instruments on Monday?

Answer:

Fraction of Time spent in playing guitar of one hour = \(\frac{2}{3}\)

Fraction of Time spent in playing guitar when finished = \(\frac{3}{4}\)

Total Time taken for practicing = \(\frac{2}{3}\) + \(\frac{3}{4}\) = \(\frac{8}{12}\) + \(\frac{9}{12}\) = \(\frac{17}{12}\) = 1\(\frac{5}{12}\) hour .

Therefore, Total Time taken in practicing = \(\frac{17}{12}\) = 1\(\frac{5}{12}\) hour

Question 3.

Ms. How bought a bag of rice for dinner. She used \(\frac{3}{5}\) kg of the rice and still had 2\(\frac{1}{4}\) kg left. How heavy was the bag of rice that Ms. How bought?

Answer:

Fraction of Quantity of rice used = \(\frac{3}{5}\) kg

Fraction of Quantity of rice left = 2\(\frac{1}{4}\) kg

Total Quantity of rice = \(\frac{3}{5}\)Â + 2\(\frac{1}{4}\)Â = \(\frac{3}{5}\) + \(\frac{9}{4}\)

= \(\frac{12}{20}\) + \(\frac{45}{20}\) =\(\frac{57}{20}\) = 2\(\frac{17}{20}\)

Therefore, Total Quantity of rice = \(\frac{57}{20}\) = 2\(\frac{17}{20}\) .

Question 4.

Joe spends \(\frac{2}{5}\) of his money on a jacket and \(\frac{3}{8}\) of his money on a shirt. He spends the rest on a pair of pants. What fraction of his money does he use to buy the pants?

Answer:

Money spent on jacket = \(\frac{2}{5}\)

Money spent on a shirt = \(\frac{3}{8}\)

Money spent on pair of pants = x

1 = \(\frac{2}{5}\) + \(\frac{3}{8}\)Â + x

lcm of 5 and 8 is 40.

\(\frac{40}{40}\) Â = \(\frac{16}{40}\) + \(\frac{10}{40}\) +x

\(\frac{40}{40}\) Â = \(\frac{26}{40}\) + x

x = \(\frac{40}{40}\)Â – \(\frac{13}{40}\)

x = \(\frac{27}{40}\)